Pengaruh Penyesuaian Rating Fuse Cut Out (FCO) Percabangan terhadap Penurunan Frekuensi Gangguan Tegangan Menengah pada Penyulang TPN06 ULP Rantau UP3 Barabai - Pandea Triaska Prasera; Pristisal Wibowo; Reza Juliangga (Jurnal Nasional Teknologi Komputer, 2026)
The reliability of medium-voltage (MV) distribution networks is strongly influenced by the performance of protection systems, particularly Fuse Cut Outs (FCO) installed at feeder branches. TPN06 feeder at PT PLN (Persero) ULP Rantau, with a total network length of 15 km and 23 distribution transformers, experienced a high disturbance frequency during August–September 2024, with 8 recorded Auto Reclose Ground Fault (AR GF) incidents. Initial evaluation revealed that most installed FCO ratings were not aligned with the actual branch load currents. Several FCOs were found to be overrated, including Pulau Kutil (4 A adjusted to 2 A), Balai Pesona (4 A to 2 A), Sei Impat (4 A to 2 A), PR Binderang (4 A to 2 A), Jati Makmur (5 A to 2 A), Budi Mulya (5 A to 3 A), and Lokpaikat (25 A to 12 A), while only Bitahan (3 A) and PR Permata (2 A) were appropriately rated. This study aims to evaluate the effectiveness of FCO rating adjustments based on actual load current measurements and three-phase apparent power calculations at 20 kV. The methodology includes disturbance data analysis, peak load current measurement using an ampere clamp, and branch current calculation. The results indicate that adjusting FCO ratings improved protection selectivity and coordination, enabling better fault localization at branch levels. Following the adjustment at the end of September 2024, the disturbance frequency significantly decreased during October–November 2024, reaching zero incidents.